Developing a sustainable practical model of graduate employability for higher education - Rufai, Ahmed Umar; Bakar, Ab. Rahim; Mat Rashid, Abdullah (Australian International Academic Centre, 2015)
The purpose of this paper is to evolve a sustainable practical model of employability skills that is sure to capture relevant learning aspects of a particular occupational discipline to be used as framework for Undergraduate students to develop their employability potentials. The study was conducted in three Universities and Polytechnics each with three multi-national companies. Data were collected using semi-structured interviews. Using purposeful sampling 18 academic staff and 3 professionals representing company employers were selected as the study participants. The study evolved a model that is work-based, explicit in its outcome, fully articulated and realistic in terms of employability skill experiences. The proposed model can be used to establish a common higher education programme or curricula that is work-based and skill experience oriented, that can encourage students in higher education to think about work place learning more explicitly and reflectively, that will in turn help them to develop a broad range of knowledge, skills, attitudes, and values, each of which ultimately contribute in some manner to graduate employability. The paper is considered a contribution to the evolution and growth of knowledge on the linkage between higher education and workplace, through which the ‘skill gap’ occurring between the demand of employment and the level of educational preparation of graduates can be bridged.